Association between social position indicators and hypertension treatment adherence in Colombia - Quiroz, Silvia Patricia; Agudelo, Diana María; Lucumi, Diego Iván; Mentz, Graciela (Revista Chilena de Salud Pública, 2020)
Introduction: To generate evidence on the effects of social position on therapeutic adherence among individuals with hypertension (HT) in Colombia. Materials and Methods: A cross-sectional study was carried out, using quantitative data from the Social Determinants and Inequities in the Control of HT Program in Colombia. Descriptive and inferential analyses (logistic regression) were developed to model the associations. Results: The prevalence of adherence was high, especially for pharmacological treat¬ment and compliance with appointments (>50%). Individuals with less education and lower income are less likely to adhere to pharmacological treatment, while tho¬se with higher socioeconomic status are less likely to adhere to appointments and healthy behaviors. Afro-Colombians were less likely to adhere to pharmacological treatment, appointments, and indications regarding physical activity. Discussion: There is a gap in HT treatment adherence in Colombia, due to socioeco¬nomic and ethnic/racial condition